Question

Simplify the expression: 43 – 6(–3*E*) – 5*E*

Tagged in

Math

Algebra

Find answers to questions asked by students like you.

Q: a? - (b + 3)2 = [a + ][a

A: The formula for difference of two squares is A2-B2=(A+B)(A-B). This can be verified by expanding the...

Q: Use the given information to find a formula for the exponential function N = N(t). N(1) = 6 and N(3...

A: In the question we have to find the equation of exponential function.

Q: Begin by graphing f(x) = 3*. Then use transformations of this graph to graph the given function. Be ...

A: Click to see the answer

Q: Drug Sensitivity The sensitivity S to a drug is relatedto the dosage size x by S = 100x - x2, where ...

A: Given : The sensitivity S to a drug is related to the dosage size by S = 100x - x2, where ...

Q: Evaluate 8 - 3 - 4

A: Given: 8-3-4 To Find: To evaluate the given expression.

Q: Solve for x

A: Given inequality is : x+1+x2-5x+1<x2-4x+3 x=-1 x=5±212 x=3, x=1 First we find intervals separatel...

Q: Identify the y-intercept of the graph ofR(x) = [ 6(x - 1) ] / [ (x + 1) (x + 2) ] . (a) - 3 (b) - 2 ...

A: Rx=6x-1x+1x+2 To find y-intercept, put x=0, we get R0=60-10+10+2=-62=-3

Q: Find an equation of the circle that satisfies the stated conditions.

A: Centre C(-3,6), tangent to the y-axis

Q: Consider the data set:4, 5, 5, 5, 6, 6, 8, 9, 11, 12What would happen to the mean if another data po...

A: First we will calculate the mean of both the data sets and then compare to find if the mean has incr...